PROBATION OF THE SOIL FROM CALEB UNIVERSITY, IMOTA LAGOS, NIGERIA AS A SOURCE OF ANTIBIOTIC-PRODUCING BACTERIA (FUDMA JOURNAL OF SCIENCES, 2024)
The importance of antibiotics in treating bacterial diseases cannot be overstated. However, the excessive use of antibiotics has led to the development of resistance in many bacteria, making the treatment of bacterial infections challenging. Therefore, it is essential to search for new strains of bacteria in different habitats that produce novel antibiotics. The aim of this study was to investigate the soil from Caleb University for antibiotic-producing bacteria. Soil samples were collected from seven locations within Caleb University, including Joshua Hall (J), Cafeteria (C), Dump site (DS), Lab garden (LAB G), Last Garden (LG), and School Inner Garden (SID). The samples were diluted, and standard procedures were followed for all experiments. The results of this study indicate that the isolated species did not show significant inhibitory activity against the test bacteria and were unable to produce antimicrobial compound. Therefore, it can be concluded that the species found in the soil samples from Caleb University are not effective in stopping bacterial growth.
Keywords: Antibiotics; Bacteria; Soil; Caleb University; Anti-microbial